Effects of Compounds from Passiflora edulis Sims f. flavicarpa Juice on Blood Coagulation and on Proteolytic Enzymes - Sato, Ana Claudia; Andrade, Sonia A.; Brito, Marlon V.; Miranda, Antonio; Sampaio, Misako Uemura; Maffei, Francisco Humberto de Abreu [UNESP]; Vilela Oliva, Maria Luiza (Bentham Science Publ Ltd, 2012)
Passion fruit (Passiflora edulis Sims f. flavicarpa) is popularly known for its sedative and calming properties and is consumed as a fresh fruit or as a juice. The clinical observation of blood incoagulability associated with excessive consumption of passion fruit juice, in a patient treated with warfarin, prompted the current study to investigate in vitro the presence of blood clotting inhibitors in Passiflora edulis Sims f. flavicarpa extract. After purification process, two compounds of distinct molecular weight and inhibitory action were better characterized. One is a trypsin inhibitor similar to inhibitors from Bowman-Birk family, named PeTI-I12, and other is a compound active in coagulation that prolongs aPTT and PT, but does not change TT. The aim of this study is to provide evidence that passion fruit extract's components play a role on hemostasis and therefore may be relevant in the handling of patients treated with anticoagulants or suffering hemorrhagic diseases.
Keywords: aPTT; blood coagulation; Bowman-Birk inhibitor; Passiflora edulis; passion fruit; Passifloraceae; trypsin inhibitor; warfarin